Evaluating Literature Review Methods in Plantae Studies: A Critical Analysis for Improved Research Synthesis - Judith Ochengo; Huijing Deng (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The literature review is an essential component of any scientific study, providing a comprehensive overview of existing knowledge in a particular field. In the realm of Plantae studies, the literature review plays a crucial role in understanding the current state of research, identifying research gaps, and formulating research questions. This article presents a critical assessment of literature review methods employed in Plantae studies, evaluating their strengths, weaknesses, and potential areas for improvement. By examining various approaches and highlighting their merits and limitations, this study aims to enhance the effectiveness and rigor of literature reviews in the field of Plantae studies.